Unusual Vermamoeba Vermiformis Strain Isolated from Snow in Mount Teide, Tenerife, Canary Islands, Spain - Reyes-Batlle, Maria; Niyyati, Maryam; M. MartÃn-Navarro, Carmen; López-Arencibia, Atteneri; Valladares, Basilio; MartÃnez-Carretero, Enrique; E. Piñero, José; Lorenzo-Morales, Jacob (Novelty in Biomedicine, 2015)
Background: Free-living amoebae (FLA) are protozoa that are widely distributed in the environment mainly in water and soil related habitats. Thermophilic amoebae are among the most common FLA in water bodies, being Vermamoeba vermiformis one of the most common species reported worldwide from these sources. Interestingly, V. vermiformis has often been reported to survive at high temperatures and osmotic pressure worldwide. Materials and Methods: In this study, snow samples were collected from Mount Teide, Tenerife, Canary Islands during the winter season of 2014. The samples were culture on non nutrient agar plates and checked daily for the presence of FLA. After a week, V. vermiformis amoebae were observed in the plates incubated at room temperature and 37ºC. Results: Molecular characterization was carried out by amplifying the 18S rDNA gene and DNA sequencing, confirmed that the isolated strain belonged to Vermamoeba vermiformis species. Conclusion: To the best of our knowledge, this is the first report of Vermamoeba vermiformis isolation from such an inusual habitat (low temperatures and high altitude) and the first report of these species in the Canary islands.